2001
DOI: 10.1002/jnr.1116
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical study of acute and chronic intraperitoneal nicotine effects on several glycolytic and Krebs cycle dehydrogenase activities in the frontoparietal cortex and subcortical nuclei of the rat brain

Abstract: The effects of nicotine on the activity of different dehydrogenases in frontoparietal regions and subcortical nuclei of the rat brain have been studied using histochemical methods. Nicotine sulphate was intraperitoneally administered in acute (4 mg/kg/day × 3 days) or chronic (ALZET osmotic pump providing 2 mg/kg/day × 15 days) doses. The enzymes analyzed were glyceraldehyde‐3‐phosphate, lactate, malate and succinate dehydrogenases (gly3PDH, LDH, MDH, and SDH, respectively). The results demonstrate that chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 93 publications
1
11
0
Order By: Relevance
“…However, a very recent study conducted in awake rats indicated a significant reduction in neuronal glucose oxidation and neurotransmitter cycle flux with 0.7 mg/kg nicotine exposure [45]. The effects of nicotine on the activity of various glycolytic and TCA cycle enzymes have been studied under acute and chronic nicotine treatments in frontoparietal regions and subcortical nuclei of the rat brain [26]. Both acute as well as chronic exposure of nicotine increases enzymatic activities in the frontoparietal cortex but deeper layers of the cortex, substantia nigra, caudate-putamen, nucleus accumbens or nucleus basalis magnocellularis did not exhibit increase in activity as high as seen in the frontoparietal cortex.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a very recent study conducted in awake rats indicated a significant reduction in neuronal glucose oxidation and neurotransmitter cycle flux with 0.7 mg/kg nicotine exposure [45]. The effects of nicotine on the activity of various glycolytic and TCA cycle enzymes have been studied under acute and chronic nicotine treatments in frontoparietal regions and subcortical nuclei of the rat brain [26]. Both acute as well as chronic exposure of nicotine increases enzymatic activities in the frontoparietal cortex but deeper layers of the cortex, substantia nigra, caudate-putamen, nucleus accumbens or nucleus basalis magnocellularis did not exhibit increase in activity as high as seen in the frontoparietal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were divided into three groups: Group (i) mice treated with normal saline (0.9% NaCl) (n = 6), Group (ii) mice treated with 0.5 mg/kg nicotine (n = 6, sc), Group (iii) mice treated with 2.0 mg/kg nicotine (n = 6, sc). Nicotine dose was selected based on previous studies where nicotine, 0.1 to 4 mg/kg, has been used in different experimental paradigms [25], [26], [32], [33], [34], [35], [36]. Mice in Group (ii) and (iii) received nicotine hydrogen tartrate (SIGMA, 0.1 ml, sc) at a dose of 1.4 and 5.7 mg/kg body weight, which is equivalent to 0.5 and 2 mg/kg nicotine free base, 3 times a day every 8 h for 4 weeks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nicotine dose administered was the same as that used in previous work showing it to be responsible for dehydrogenase activation and NGF induction, but not the induction of apoptosis. 13,14 We have previous information on the minimum amphetamine dose inducting apoptosis in the hippocampus using a similar treatment schedule as here. Here, the selected dose was 75% lower than in that study in order to prevent apoptosis.…”
Section: Experimental Animalsmentioning
confidence: 99%
“…Some of the effects of this drug are positive, such as neuroprotection against neurotoxic agents, ageing, and pathological situations. [6][7][8][9][10][11][12] Our research group has demonstrated that nicotine increases the turnover of the glycolytic pathway and Krebs cycle in neurons, 13 and the NGF immunoreactivity in the frontoparietal cortex. 14 The benefits of other changes, such as the modification of synaptic transmission 15 and the activation of the midbrain dopamine system, 16 are more debatable.…”
Section: Introductionmentioning
confidence: 99%